2002
DOI: 10.1287/opre.50.4.670.2857
|View full text |Cite
|
Sign up to set email alerts
|

A Bi-Objective Median Location Problem With a Line Barrier

Abstract: The multiple objective median problem (MOMP) involves locating a new facility with respect to a given set of existing facilities so that a vector of performance criteria is optimized. A variation of this problem is obtained if the existing facilities are situated on two sides of a linear barrier. Such barriers, like rivers, highways, borders, or mountain ranges, are frequently encountered in practice. In this paper, theory of an MOMP with line barriers is developed. As this problem is nonconvex but specially s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…In Klamroth (2001a,b) it was shown that an optimal solution of the non-convex barrier problem can be found by solving a finite and, in the case of line barriers, polynomial number of related unconstrained subproblems, a result which will be used extensively in this paper. A generalization to multi-criteria problems was discussed in Klamroth and Wiecek (2002).…”
Section: Introductionmentioning
confidence: 99%
“…In Klamroth (2001a,b) it was shown that an optimal solution of the non-convex barrier problem can be found by solving a finite and, in the case of line barriers, polynomial number of related unconstrained subproblems, a result which will be used extensively in this paper. A generalization to multi-criteria problems was discussed in Klamroth and Wiecek (2002).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of line barriers, Klamroth [10] considered a limited number of passages with any distance measure, separated the plane into two sub-planes and showed that an optimal solution of the non-convex barrier problem can be attained by solving a polynomial number of related unconstrained sub-problems. Klamroth and Wiecek [11] generalized this result to multi-criteria problems. Huang et al [12] find the optimal location of k connections in the plane for uncapacitated and capacitated location problems.…”
Section: Introductionmentioning
confidence: 91%
“…For the case of polyhedral barrier sets, Klamroth (2001a) and Klamroth (2001b) showed that an optimal solution of the non-convex barrier problem can be found by solving a finite (and in the case of line barriers a polynomial) number of related unconstrained subproblems. This result was generalized to the multi-criteria case in Klamroth and Wiecek (2002).…”
Section: Introductionmentioning
confidence: 91%